Ischemia Induces Release of Endogenous Amino Acids from the Cerebral Cortex and Cerebellum of Developing and Adult Mice - Oja, Simo S. (Hindawi Publishing Corporation, 2013)
Ischemia enhanced release of endogenous neuroactive amino acids from cerebellar and cerebral cortical slices. More glutamate was released in adult than developing mice. Taurine release enhanced by K(+) stimulation and ischemia was more than one magnitude greater than that of GABA or glutamate in the developing cerebral cortex and cerebellum, while in adults the releases were almost comparable. Aspartate release was prominently enhanced by both ischemia and K(+) stimulation in the adult cerebral cortex. In the cerebellum K(+) stimulation and ischemia evoked almost 10-fold greater GABA release in 3-month olds than in 7-day olds. The release of taurine increased severalfold in the cerebellum of 7-day-old mice in high-K(+) media, whereas the K(+)-evoked effect was rather small in adults. In 3-month-old mice no effects of K(+) stimulation or ischemia were seen in the release of aspartate, glycine, glutamine, alanine, serine, or threonine. The releases from the cerebral cortex and cerebellum were markedly different and also differed between developing and adult mice. In developing mice only the release of inhibitory taurine may be large enough to counteract the harmful effects of excitatory amino acids in ischemia in both cerebral cortex and cerebellum, in particular since at that age the release of glutamate and aspartate cannot be described as massive.